2018
DOI: 10.1038/s41598-018-33188-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Arousal Patterns of Identical Twins with Discordant Sexual Orientations

Abstract: Genetically identical twins can differ in their self-reported sexual orientations. However, whether the twins’ subjective reports reflect valid differences in their sexual orientations is unknown. Measures of sexual orientation, which are free of the limitations of self-report, include genital arousal and pupil dilation while viewing sexual stimuli depicting men or women. We examined these responses in 6 male twin pairs and 9 female twin pairs who reported discordant sexual orientations. Across measures, heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Participants for the constituent studies were recruited by researchers at four sites: Northwestern University in Evanston, IL (6,11,12,29), the Centre for Addiction and Mental Health in Toronto, Ontario, Canada (18), the University of Essex in Colchester, UK (15,30), and Cornell University in Ithaca, NY (17). Individual sample sizes and methodological differences between the studies are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants for the constituent studies were recruited by researchers at four sites: Northwestern University in Evanston, IL (6,11,12,29), the Centre for Addiction and Mental Health in Toronto, Ontario, Canada (18), the University of Essex in Colchester, UK (15,30), and Cornell University in Ithaca, NY (17). Individual sample sizes and methodological differences between the studies are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“… Education data were available for 359 participants; educational attainment was not recorded in Jabbour et al ( 29 ), Watts et al ( 30 ), or Slettevold et al ( 15 ). Education was coded as 1 (no high school), 2 (some high school), 3 (high school diploma), 4 (some college), 5 (college graduate), or 6 (postgraduate student or degree).…”
Section: Methodsmentioning
confidence: 99%
“…For cisgender men, the relationship (β) of their sexual attraction with their genital sexual arousal to male or female sexual stimuli falls between 0.80 and 0.90 (Rieger et al, 2015; Watts et al, 2018). Thus, significant power of 80% can be achieved with a minimum of nine cisgender men with different sexual attractions.…”
Section: Methodsmentioning
confidence: 99%
“…There is concern that self-report measures of sexual arousal may have limited validity. As such, Watts et al (2018) conducted a twin study of sexual arousal that used two physiological measures, namely genital arousal and pupil dilation, when viewing sexual stimuli showing males or females. The sample included six MZ male twin pairs and nine MZ female twin pairs, all discordant for self-reported sexual orientation.…”
Section: Sexual Arousal Patterns In Mz Twins Discordant For Sexual Ormentioning
confidence: 99%
“…Finally, the results from the physiological measures aligned with the twins' self-reported sexual preferences. Watts et al (2018) speculated that a combination of epigenetic and prenatal hormonal influences might explain their results.…”
Section: Sexual Arousal Patterns In Mz Twins Discordant For Sexual Ormentioning
confidence: 99%